Metode Material Requirement Planning (MRP) dalam Perencanaan Produksi Sirup Markisa Dewi - Anastasya Bernike Br Ginting; Asima Manurung; Sutarman Sutarman; Enita Dewi Br Tarigan (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This study examines the Material Requirement Planning (MRP) method in planning the production of Dewi Passion Fruit syrup. Through a literature study approach, collecting articles or journals related to production planning, determining order size and MRP. The results showed that the results of forecasting the demand for passion fruit syrup were 87,751 liters with passion fruit raw materials of 175,502 kg and sugar of 87,751kg. As well as based on the Material Requirement Planning (MRP) method and lot sizing techniques which include Silver Meal Algorithm and Wagner Within Algorithm, the one used in this study is Silver Meal Algorithm because it has a smaller total order cost and storage cost than Wagner Within Algorithm.